2019
DOI: 10.1155/2019/5707150
|View full text |Cite
|
Sign up to set email alerts
|

Inulin Supplementation Reduces Systolic Blood Pressure in Women with Breast Cancer Undergoing Neoadjuvant Chemotherapy

Abstract: Introduction. Breast cancer is the most frequently diagnosed malignancy in women, and comorbidities like hypertension and obesity diminish their quality of life and negatively affect their response to chemotherapy. Furthermore, inulin supplementation is associated with the reduction of cardiovascular diseases (CVD) risk. Objective. To determine whether inulin supplementation prevents the elevation of blood pressure in women with breast cancer undergoing neoadjuvant therapy with cyclophosphamide and doxorubicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Selection criteria were performed by five studies (six arms) [10,13,15,16] with all 233 participants. The exact steps of the selection process are summarized in Figure 1…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…Selection criteria were performed by five studies (six arms) [10,13,15,16] with all 233 participants. The exact steps of the selection process are summarized in Figure 1…”
Section: Literature Searchmentioning
confidence: 99%
“…Chosen studies were carried out in Iran [10,16] Spain [13] and Mexico. [15] A parallel design used for all the studies. The study duration varied between 3 and 8.5 weeks.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The supplementation lasted for 21 days at the same time as they underwent chemotherapy with doxorubicin and cyclophosphamide for the first time. The study found that inulin supplementation had a significant reduction in SBP of 4.21 mmHg ( p < 0.001) and no significant changes regarding DBP [ 67 ].…”
Section: Resultsmentioning
confidence: 99%